Impact of a videoconferencing educational programme for the management of concurrent disorders on nurses’ competency development and clinical practice: protocol for a convergent mixed methods study - Pierre Pluye; Guillaume Fontaine; José Côté; Didier Jutras-Aswad; Gabrielle Chicoine; Jacinthe Pépin; Louise Boyer; Geneviève Rouleau; Simon Dubreucq (BMJ Open)
Introduction Extension for Community Healthcare Outcomes (Project ECHO©) is an innovative model for continuing professional development that uses videoconferencing technology to support and train general practitioners remotely. The model has been replicated to a variety of settings and locations for capacity building in healthcare professionals caring for patients with chronic and complex health conditions. Limited research has been conducted so far on the impact of ECHO in the field of concurrent mental health and substance use disorders (ie, concurrent disorders (CDs)). Therefore, this mixed methods study aims to develop a comprehensive understanding of an ECHO programme impact for CD management on nurses’ competency development and clinical practice.Methods and analysis The proposed mixed methods study, based on a convergent parallel design, will be conducted in the province of Quebec, Canada, to collect, analyse and interpret quantitative (QUAN) and qualitative (QUAL) data from a specific ECHO Program on CDs. In the QUAN component, an observational prospective cohort study will be conducted over a 12-month period. All nurses who participated in the programme between 2018 and 2020 and who consent to research will be recruited to collect data on the extent of their learning and practice outcomes at three time points. Alongside the surveys, nurses will be invited to participate in individual semistructured interviews. In-depth QUAL data will be subjected to a thematic analysis and will assist in exploring how and in which conditions nurses developed and mobilised their competencies in clinical practice. A comparison-of-results strategy will be used in the final integration component of the study.Ethics and dissemination This study protocol was approved by the Ethics Committee of the Université de Montréal Hospital Center (#19.295) and the Université de Montréal Ethics Committee (CERSES-20–017 R). We aim to disseminate the findings through international academic conferences, international peer-reviewed journals and professional media.